Islamic perspective of stock market an analysis based on Shari`ah principles - Osmani, Noor Mohammad; Abdullah, Faruk (2009)
There is no denying to the fact that the stock market is an integral part of the economic development of a nation. The current economic crisis was largely due to the fall of the giant global stock exchanges in New York, Europe, Japan and others. As the world today looks for an alternative for the capitalistic economy, and considering Islamic financial system as its powerful alternative, there is an urge to find out the legal status of the conventional stock market in Islamic shari`ah. The purpose of this paper therefore is to provide a theoretical framework for Islamic stock market and to see the validity of the existing products in the conventional stock markets such as common shares, preferred shares, short selling, margin trading, options, futures and the bonds etc. It would examine if the existing products conform to Shari`ah principles of prohibition of Riba, Gharar, Maysir, Qimar and maintaining fairness in price and so on. The paper adopts an inductive and analytical method to examine issues based on the traditional texts and modern literatures. It is expected that the paper will reach some conclusions and provide clear recommendations to provide an Islamic alternative to the conventional stock and securities market.